Nilai-Nilai Ajaran Luhur Ki Hajar Dewantara (International Forum of Researchers and Lecturers, 2024)
Ki Hadjar Dewantara's thoughts on contributions to education in Indonesia, with a special emphasis on educational goals and curriculum. According to Ki Hadjar Dewantara, the purpose of education is to develop each person's potential in terms of intellectual, moral, and social aspects. He emphasized the importance of education rooted in culture, principles, and society. The proposed curriculum integrates character development and academic elements as a whole. The results of this study show that education based on the teachings of Ki Hadjar Dewantara can produce a generation that is not only intellectually smart but also possesses high morality and social responsibility. Therefore, it is hoped that education based on the principles of Ki Hadjar Dewantara will contribute to the development of the nation's character and culture.